Contribuições de projetos formativos desenvolvidos no Projeto Sala de Educador ao ensino de ciências do 1° e 2° ciclos - Ribeiro, Josiani Leitner (2016)
In this work, the subject of research was the contributions of training projects developed via Educator room for the Science Education 1st and 2nd cycles, the state schools in Tangará da Serra – Mato Grosso. Methodologically, we use the literature review, document analysis that included four years from 2010 to 2013; and finally, the field research, using semi-structured interview technique, applied to 34 teachers who work in the phases that make up the 1st cycle to the 2nd stage of the 2nd cycle of the 10 schools surveyed. For qualitative data analysis was applied to content analysis technique categorization and description of frequency. The main aim was to investigate how to configure the subjects of science teaching in continuing education activities of teachers developed the Educator room checking if there were contributions that caused significant changes in teaching practice in science teaching. For this action, an educational product developed was developed through: Continuing Training Workshop in Science Teaching for 1st and 2nd cycles of teachers, with a workload of 50 hours. With the data analysis, it was inferred that the educational product contributed the teachers through continuing education, develop significantly their pedagogical with the students. In summary, the data showed that one of the possible ways to implement the teaching of science in schools is to use the investigative approach and provide meaningful activities for students.